The Italian Contribution to Manchester. (May 2015) - Rea, Anthony
Abstract : This project looks for evidence that the Italian people have made a valuable contribution to the city of Manchester, UK. It examines the following areas: the Roman settlement of Manchester; the first wave of immigration in the late 1700s of professional and highly skilled Italians, predominantly from northern Italy; the second wave of immigrants after Italian unification in 1861, mainly from the 'contadini' or farming classes of Italy; the Italian pioneers of the ice cream industry in Manchester; prominent Italian figures in the city's musical culture; notable names of the highly skilled terrazzo and mosaic workers, carvers, and sculptors who worked in the city; the Italian community's devotion to religion; influence on football; service to the armed forces; and creation of businesses from post-war to modern day. By providing concise evidence of Italian activity in these areas, the conclusion is reached that Italian immigrants have made a significant positive contribution to the city.